The third wheel - Kinney, Jeff (Kinney, Jeff. Diary of a wimpy kid (Series) ;)
Greg Heffley is not willing to be the odd man out. A dance at Greg's middle school has everyone scrambling to find a partner, and Greg is determined not to be left by the wayside. So he concocts a desperate plan to find someone -- anyone! -- to go with on the big night. But Greg's schemes go hilariously awry, and his only option is to attend the dance with his best friend, Rowley Jefferson, and a female classmate as a "group of friends." But the night is long, and anything can happen along the way. Who will arrive at the dance triumphantly, and who will end up being the third wheel?